The association of maternal pre-pregnancy body mass index with breastfeeding initiation - نعيسة, ثورة; سلمان , صفاء; محمد, خناف (Latakia University Journal -Medical Sciences Series, 2021)
Objective: evaluate incidence of breastfeeding initiation according to maternal pre-pregnancy body mass index (BMI) in the first 48 hours postpartum. Patients and methods: A prospective cohort study included 101 pregnant women with a single live pregnancy. The BMI pre-pregnancy was calculated and divided ​​into 4 groups. Log-binomial regression analyses were performed to assess relative risk (RR) of non-initiation of breastfeeding between maternal BMI categories after exclusion of variables with a mediating effect. The duration of the research was one year, from February 2020 to February 2021. Results: Breastfeeding was initiated among 81.2% of the research sample. 83.6% of normal weight women started breastfeeding compared to 64.7% of obese women (RRunadj 3.4 95% CI [1.7-5.9]). The obese group remained less likely to initiate breastfeeding even after adjusting for prenatal, perinatal and neonatal factors (RRadj 2.3 95% CI [1.2-3.1]). Conclusion: obese women are twice less likely than normal weight women to initiate breastfeeding in the immediate postpartum period.